Long‐term efficacy of polydimethylsiloxane (Macroplastique®) injection for Mitrofanoff leakage after continent urinary diversion surgery. (20th October 2014) - Kass‐iliyya, Antoine; Rashid, Tina G.; Citron, Isabella; Foley, Charlotte; Hamid, Rizwan; Greenwell, Tamsin J.; Shah, P. Julian R.; Ockrim, Jeremy L.
<x xml:space="preserve">Abstract</x> Objective To assess the long‐term efficacy of polydimethylsiloxane (Macroplastique®) injection (MPI) in the treatment of Mitrofanoff leakage secondary to valve incompetence. Patients and Methods Between 1995 and 2012, the records of 24 consecutive patients who underwent MPI for Mitrofanoff urinary leakage after continent cutaneous urinary diversion (CCUD) surgery were examined. All patients had a valve deemed of sufficient length (>2 cm) to attempt Macroplastique coaptation. Treatment outcomes were divided into three categories based on physician assessment: success (dry), partial success (>50% reduction in incontinence pads) and failure. Success rates were assessed according to the type of reservoir and conduit channel. Results The mean (range) follow‐up was 30 (6–96) months. One patient had initial difficulty catheterising, and subsequently required major revision surgery. In all, 12 patients (50%) failed the treatment and subsequently underwent operative revision to the channel. Three patients (12.5%) achieved complete success; one patient had an appendix channel through native bladder and the remaining two had Monti channels through colon. Nine patients (37.5%) had partial success; success rates were higher with appendix channels (four of six) and colonic reservoirs (six of seven) when compared with Monti channels (eight of 18, 44%) and ileal reservoirs (zero of two). Five of the nine patients with partial success eventually required further surgical revision for deteriorating continence at a mean (range) of 41 (14–96) months, whilst the other four have maintained sufficient continence with MPI alone. Conclusion Macroplastique bulking cured only 12.5% patients, but leakage was substantially improved in a further 37.5% allowing major surgery to be avoided or postponed in one half of the cohort. Appendix Mitrofanoffs do better than the Monti Mitrofanoff, with channels through colonic segments generally doing better than those through ileal bladders. MPI should be considered as a less invasive alternative to avoid or delay major reconstructive surgery.